“In a Sea of Fire, in a Rain of Bombs.” Jewish Children in Warsaw during September 1939 Siege - Eyal Ginsberg (Acta Universitatis Carolinae Studia Territorialia)
The German invasion of Poland on September 1, 1939, led to the rapid evacuation of the Polish government from Warsaw, with the city eventually surrendering to the Nazis on September 28. The devastating aftermath saw a quarter of Warsaw’s houses destroyed and approximately 50,000 people killed or wounded. This article focuses on the experiences of Jewish children during this tumultuous period, a subject often overlooked in historical literature. While extensive research exists on children in Warsaw, particularly during the Ghettoization period, little attention has been given to the crucial initial month marked by both land and air assaults. Drawing from diverse sources such as diaries, archival materials, and oral testimonies, this article provides a comprehensive understanding of how Jewish children navigated the challenges of the siege and their survival strategies. By synthesizing these perspectives, it offers a nuanced analysis of their experiences, shedding light on an important aspect of this historical event.